2009
DOI: 10.1111/j.1365-2559.2009.03323.x
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of MAP kinase pathway alterations in KIT and PDGFRA wild‐type GISTs

Abstract: In the absence of RAS mutations, MAPK could be activated through SCF/KIT autocrine/paracrine mechanisms and/or mutated BRAF in a subset of KIT/PDGFRA wild-type GISTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 48 publications
0
25
1
Order By: Relevance
“…12,[18][19][20] In addition, the BRAF mutation status was evaluated in KIT/PDGFRA wild-type GISTs (n = 9) from Barretos Cancer Hospital and the SDH genes status was evaluated in KIT/PDGFRA/BRAF wildtype GISTs (n = 18) from Centro Hospitalar S. João. 15,16 Tumor genomic DNA was extracted from formalin-fixed and paraffinembedded tissues using the QIAamp DNA MicroKit (Qiagen, Hilden, Germany), following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…12,[18][19][20] In addition, the BRAF mutation status was evaluated in KIT/PDGFRA wild-type GISTs (n = 9) from Barretos Cancer Hospital and the SDH genes status was evaluated in KIT/PDGFRA/BRAF wildtype GISTs (n = 18) from Centro Hospitalar S. João. 15,16 Tumor genomic DNA was extracted from formalin-fixed and paraffinembedded tissues using the QIAamp DNA MicroKit (Qiagen, Hilden, Germany), following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumor on the gastrointestinal tract characterized by hotspot mutations in KIT and PDGFRA genes, which are predictive of imatinib-based therapy response. 10,11 Somatic BRAF mutations [12][13][14] and germinative SDHx mutations were reported in a subset of KIT/PDGFRA wild-type GIST. 15,16 Increased telomerase activity was reported in GISTs and was associated with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent paper by Lasota et al reported about the absence of KRAS mutations in a large cohort of GISTs (n =514) [3] which, to the best of our knowledge, constitutes by itself about 60 % of cases so far studied for this molecular alteration [4][5][6][7]. Thus, considering the cumulative evidence produced so far, the actual possible prevalence of KRAS mutations in GISTs seems much lower than the one we hypothesized, possibly approaching 0.3 %.…”
mentioning
confidence: 50%
“…The first studies indicating an alternative pathway involved in GIST tumorigenesis were related to a molecular alteration occurring in the mitogen-activated protein kinase pathway: BRAF V600E somatic mutation was reported in 3-7% KIT/PDGFRA WT GISTs [17][18][19] and in one KIT-mutated GISTs. 20 Recently, loss of function of succinate dehydrogenase (SDH) complex was proposed as another alternative molecular mechanism in KIT/PDGFRA/BRAF WT GISTs.…”
Section: Introductionmentioning
confidence: 99%